Activating mitochondrial function and haemoglobin expression with EH‐201, an inducer of erythropoietin in neuronal cells, reverses memory impairment - Horng, Lin‐Yea; Hsu, Pei‐Lun; Chen, Li‐Wen; Tseng, Wang‐Zou; Hsu, Kai‐Tin; Wu, Chia‐Ling; Wu, Rong‐Tsun (British journal of pharmacology, 2015)
Background and Purpose Memory impairment can be progressive in neurodegenerative diseases, and physiological ageing or brain injury, mitochondrial dysfunction and oxidative stress are critical components of these issues. An early clinical study has demonstrated cognitive improvement during erythropoietin treatment in patients with chronic renal failure. As erythropoietin cannot freely cross the blood–brain barrier, we tested EH‐201 (2,3,5,4′‐tetrahydroxystilbene‐2‐O‐β‐d‐glucoside, also known as TSG), a low MW inducer of erythropoietin, for its therapeutic effects on memory impairment in models of neurodegenerative diseases, physiological ageing or brain injury. Experimental Approach The effects of EH‐201 were investigated in astrocytes and PC12 neuronal‐like cells. In vivo, we used sleep‐deprived (SD) mice as a stress model, amyloid‐β (Aβ)‐injected mice as a physiological ageing model and kainic acid (KA)‐injected mice as a brain damage model to assess the therapeutic effects of EH‐201. Key Results EH‐201 induced expression of erythropoietin, PPAR‐γ coactivator 1α (PGC‐1α) and haemoglobin in astrocytes and PC12 neuronal‐like cells. In vivo, EH‐201 treatment restored memory impairment, as assessed by the passive avoidance test, in SD, Aβ and KA mouse models. In the hippocampus of mice given EH‐201 in their diet, levels of erythropoietin, PGC‐1α and haemoglobin were increased Conclusions and Implications The induction of endogenous erythropoietin in neuronal cells by inducers such as EH‐201 might be a therapeutic strategy for memory impairment in neurodegenerative disease, physiological ageing or traumatic brain injury.